Tourism: Dépense or Creative Consumption? - Volli, Ugo (E|C, 2022)
The paper proposes to reconsider the semiotics of tourism by privileging not the point of view of the tourist offer, that is of the entrepreneurs, of the managers of the places, ultimately of the communication and promotion of tourism, but that of the tourist "demand", that is of the same travelers. In fact, it is clear that historically it is almost always travelers who create the attraction of places, who "invent them". The paper considers in particular the example of the letters of Francesco Petrarca. Going deeper into the problem a little, a significant fact emerges: far any tourist activity, the traveler incurs a cast (economic, time, physical effort) to obtain in exchange a value that interests him, whether it is entertainment or culture, health or landscape. Tourism thus reveals itself to the serniotic eye as a work of exchange between values. Two models are suggested far the analysis of this exchange: that of sacrifice, which by consecrating things establishes the value of divinities, and that of Bataille's "depense", where destruction is a condition far the affirmation of the subject.